Putting ourselves back in the equation : why physicists are studying human consciousness and AI to unravel the mysteries of the universe - Musser, George (Farrar, Straus and Giroux, 2023)
"An exploration of the interconnections between quantum mechanics, cosmology, and neuroscience"--